A novel Ge based overlapping gate dopingless tunnel FET with high performance. (11th September 2019) - Chen, Shupeng; Liu, Hongxia; Wang, Shulong; Han, Tao; Li, Wei; Wang, Xing
Abstract: In this letter, the overlapping gate dopingless tunnel field-effect transistor (OGDL-TFET) is proposed and studied by TCAD simulation. To increase the tunneling efficiency and reduce the manufacture difficulty, a dopingless germanium tunneling junction based on charge plasma concept is induced in OGDL-TFET. A high efficiency line tunneling junction is formed by the gate/backgate overlap. The on-state current of 75.5 μ A μ m −1 and subthreshold swing of 1.9 mV/dec can be obtained. With cut-off frequency of 16.53 GHz and gain bandwidth product of 2.44 GHz, OGDL-TFET obtains good analog and radio frequency performance. The considerable good performance makes OGDL-TFET very attractive for ultra-low power application.